2019
DOI: 10.1177/1558925019890340
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic hydrothermal synthesis of xonotlite fibers by alkali silica extraction of fly ash

Abstract: The silica leached from coal fly ash using alkali, via the hydrothermal method, can be used as the raw material for the synthesis of xonotlite fibers through the hydrothermal synthesis method. This investigation was made to examine how the fly ash desilicated liquid influences the crystal growth and microstructure of xonotlite fibers. The obtained samples were characterized by X-ray diffraction and scanning electron microscope techniques to investigate their mineralogical composition and morphological characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In addition, a turbid Ca(OH) 2 solution can be used to obtain Xonotlite fibers using a single precipitation method. 99 Moreover, transformation processes have been observed; during precipitation, the pore structure and shape of samples vary from nonporous to wedge-shaped, slit-shaped, and cylinder-shaped mesostructures with an increase in reaction intensity. 44 Precipitation can be conducted under acidic or basic conditions with the acid and base as precipitators; these two pathways yield differences in the product.…”
Section: ■ Synthesis Of Porous Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, a turbid Ca(OH) 2 solution can be used to obtain Xonotlite fibers using a single precipitation method. 99 Moreover, transformation processes have been observed; during precipitation, the pore structure and shape of samples vary from nonporous to wedge-shaped, slit-shaped, and cylinder-shaped mesostructures with an increase in reaction intensity. 44 Precipitation can be conducted under acidic or basic conditions with the acid and base as precipitators; these two pathways yield differences in the product.…”
Section: ■ Synthesis Of Porous Materialsmentioning
confidence: 99%
“…Similarly, alkalis can be used to extract elements from CFA. However, most hydroxides in CFA cannot be dissolved in water, and alkali dissolution is rarely used for extracting elements from CFA, except for amorphous Si and Al due to their special characteristics. , Our previous study of Si extraction using sodium hydroxide (NaOH) showed that the efficiency of Si extraction increased as the reaction temperature rose from 80 to 110 °C; however, further temperature increases led to the formation of the byproduct hydroxy-sodalite. Other techniques (e.g., ultrasound) have been used to shorten the reaction time and have been reported to improve the extraction efficiency from 34.96% to 54.42% .…”
Section: Elemental Extraction Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our method involves a two‐stage treatment of CFA: (1) a thermal activation phase where CFA is mixed with Na 2 CO 3 at various ratios and subsequently calcined at different temperatures, and (2) an HCl‐based acid reflux process to isolate silica as a residual product after filtration. The utilization of Na 2 CO 3 guarantees the extraction of silica as a residue, in contrast to the NaOH technique described by Peng [10] and Ju et al., [11] which results in solubilization of silica. This approach enhances reactivity, improving the leaching of unwanted components during acid leaching and increasing the purity of the synthesized silica.…”
Section: Introductionmentioning
confidence: 99%